NON-GENETIC FACTORS INFLUENCING INTERNAL EGG QUALITY TRAITS IN CHICKEN: A REVIEW - Supral A.; Surya P.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Poultry eggs are used as breakfast meals in every corner of the world due to its easy availability and affordability; majorly being a rich source of protein. The nutritional component of an egg is purely determined by internal egg quality (albumen and yolk). This review paper thus focuses on the non-genetic factors affecting the internal egg quality characters of table eggs. The aim of this review paper is to address and improve the internal egg quality ensuring good quality albumen. Different journals were searched and studied on related topics before starting the review. The journals were selected from different parts of the world randomly visualizing the overall condition of poultry eggs and their internal egg quality characters. Haugh unit is regarded as the standard measurement of the albumen quality while color characteristics of yolk are regarded as the measurement standards. The protein content of albumen is mainly affected by the age of hens; the impact of different diseases and storage duration and conditions (temperature and humidity). Increasing the age of hens results in a lowering of the albumen index and albumen quality along with the lowering of egg production. Carotene content in feed ingredients gives better yolk color and yolk characteristics; high lysine and ascorbic acid resulting in better albumen quality to some extent. Vitamin A supplementation along with feed has shown a somewhat decreased incidence of blood and meat spots. The Haugh Units significantly decrease with the storage period but this declining quality can be minimized by maintaining low-temperature storage conditions up to 7-10 days. Eggs are a rich source of protein consumed in daily life in every household. Eggs are selected by visualizing the external eggshell quality but the internal albumen quality is very important because the protein content solely depends upon albumen. Thus the researches should be conducted for improving the internal egg quality characters.